1991
DOI: 10.1007/bf00011873
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of iron acquisition from siderophores by microorganisms and plants

Abstract: Most bacteria, fungi, and some plants respond to Fe stress by the induction of high-affinity Fe transport systems that utilize biosynthetic chelates called siderophores. To competitively acquire Fe, some microbes have transport systems that enable them to use other siderophore types in addition to their own. Bacteria such as Escherichia coli achieve this ability by using a combination of separate siderophore receptors and transporters, whereas other microbial species, such as Streptomyces pilosus, use a low sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
76
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(78 citation statements)
references
References 52 publications
1
76
0
1
Order By: Relevance
“…1a online). Apparently, this strain is highly adapted to obtaining chelated iron from other sources, as fungi and monocotyledonous plants also produce siderophores 22 . The high number of putative receptors suggests a role not only for rhizosphere competence of strain BH72, but also for biocontrol.…”
Section: Iron-transport Related Proteinsmentioning
confidence: 99%
“…1a online). Apparently, this strain is highly adapted to obtaining chelated iron from other sources, as fungi and monocotyledonous plants also produce siderophores 22 . The high number of putative receptors suggests a role not only for rhizosphere competence of strain BH72, but also for biocontrol.…”
Section: Iron-transport Related Proteinsmentioning
confidence: 99%
“…This mechanism is supported by Crowley et al in 1991 [2]. However, due to metal ions' charge, lipohilic cellular membrane would be the first barrier of ions' entrance into cells.…”
Section: Accumulation and Transportmentioning
confidence: 79%
“…Different from other organic pollutants, hazardous heavy metals are indestructible, as they cannot be chemically or biologically degraded. Even worse, some heavy metals can concentrate along the food chain and eventually accumulate in human body because we are at the top of the food chain [1][2][3]. Therefore increasing attention has been paid in recent years to the remediation of polluted soils, among which the use of plants and microbes to remove hazardous metal ions is particularly emphasized [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of plant species have the ability to acquire Fe from MS, such as PSB, coprogen, ferrichrome A, and FeFOB (Jurkevitch et al, 1986(Jurkevitch et al, , 1988Crowley et al, 1991). Among plant species reported were peanut and cotton (Bar-Ness et al, 1991), oat (Powell et al, 1982;Reid et al, 1984;Crowley et al, 1988), sorghum and sunflower (Cline et al, 1984), and cucumber (Wang et al, 1993).…”
mentioning
confidence: 99%
“…Wang et al (1993) found a direct and specific utilization of FeFOB by cucumber plants. Crowley et al (1988Crowley et al ( , 1991 reported on the direct and specific utilization of hydroxamate siderophores by oat plants. In contrast, Bar-Ness et al (1992) and Crowley et al (1992) showed that Fe supplied as FeFOB to maize plants is mainly taken up by rhizoplane bacteria, which compete with the plants for Fe.…”
mentioning
confidence: 99%